An empirical study of customer loyalty towards Islamic private pre-school: Tadika Cinta Bestari Enterprise / Lily Muliana Mustafa - Mustafa, Lily Muliana (2013)
The purpose of this study was to prove the relationship between customer loyalty of Tadika Cinta Bestari Enterprise; an Islamic private pre-school with teacher quality, safety and security and cost affordability. Parents of Tadika Cinta Bestari Enterprise with different age and professional level were used as a respondent in this study. The sample size comprises of 40 customers who used to send their children to this Islamic private kindergarten. Respondents were asked to rate their teacher quality, safety and security and cost affordability on Tadika Cinta Bestari Enterprise towards customer loyalty in a form of questionnaires which were written in Malay and English. Various data analysis tools have been used to analyze the data such as frequency analysis, descriptive analysis, reliability analysis, Pearson’s correlation and Duncan multiple range test. As a whole, all independent variables which are teacher quality, safety and security, and cost affordability have a significant relationship with customer loyalty. This study will intends to prove that the role of these three independent variables in increasing the customer loyalty of Tadika Cinta Bestari Enterprise. It is also to determine which variables give the strongest effect on customer loyalty.